Administrators violating laws and regulations, their causes and ways to reduce them "A field study applied to a sample of administrators in the schools of the first cycle of basic education in the city of Latakia" - غانم, ثناء; رباب أسود , (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the research is to identify the most common violations of laws and regulations by administrators in schools of the first cycle of basic education, and the rates of prevalence and determine their causes and ways to reduce them. To achieve the objectives of the research, the descriptive approach was adopted and the questionnaire was used as a research tool and applied to a sample of 50 administrators. The results of the research showed that the most common violations are the failure to restrict administrators to work, unfairness in the distribution of work, ignoring the delay and absence of some teachers, and evasion of work despite their presence in school. The reasons for most of the violations are due to sympathy with humanitarian cases, taking into account the difficult economic and social situation of teachers, and to achieve personal gains (material or moral), and one of the most important ways to reduce violations is to strictly apply laws and regulations, along with spreading a culture of the rule of law among workers in the educational sector and improving their living conditions.